2016
DOI: 10.1155/2016/5726465
|View full text |Cite
|
Sign up to set email alerts
|

UnderstAID, an ICT Platform to Help Informal Caregivers of People with Dementia: A Pilot Randomized Controlled Study

Abstract: Information and communications technology (ICT) could support ambient assisted living (AAL) based interventions to provide support to informal caregivers of people with dementia, especially when they need to cope with their feelings of overburden or isolation. An e-learning platform (understAID application) was tested by informal caregivers from Denmark, Poland, and Spain to explore the technical and the pedagogical specifications, as well as evaluating the impact of its use on the psychological status of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(151 citation statements)
references
References 41 publications
3
141
0
3
Order By: Relevance
“…In total 28 original studies were identified that tested an intervention comprising solely of peer support or had a peer support component. We examined the extent, nature and distribution of the studies included in this review and determined the following: the majority of studies ( n = 12) used a trial design including randomised controlled trials, pragmatic randomised trials, randomised controlled evaluations, randomised controlled two group design or randomised pilot studies (Charlesworth et al, ; Finkel et al, ; Gaugler et al, , , , ; Gaugler, Reese, Reese, & Mittelman, ; Hayden, Glynn, Hahn, Randall, & Randolph, ; Laakkonen et al, , ; Lai et al, ; Martindale‐Adams, Nichols, Burns, Graney, & Zuber, ; Mittelman et al, ; Núñez‐Naveira et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ; Winter & Gitlin, ), eight studies used a pre/post‐test design (Boots, de Vugt, Withagen, Kempen, & Verhey, ; Chenoweth et al, ; Chu et al, ; Dam, van Boxtel, Rozendaal, Verhey, & de Vugt, ; Gaugler, Hobday, et al, ; Hsu et al, ; Javadpour, Ahmadzadeh, & Bahredar, ; O'Connor, Arizmendi, & Kaszniak, ), four a quasi‐experimental design (Andren & Elmståhl, , ; Easom, Alston, & Coleman, ; Marziali & Garcia, ; Pagán‐Ortiz, Cortés, Rudloff, Weitzman, & Levkoff, ), two a quasi‐experiment with mixed methods design (Baily, Kingsyon, Alford, Taylor, & Tolhurst, ; Küçükgüçlü, Akpınar Söylemez, Yener, & Işık, ) and the final two studies used mixed methods (Hattink, Droes, Sikkes, Oostra, & Lemstra, ; McKechnie, Barker, & Stott, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total 28 original studies were identified that tested an intervention comprising solely of peer support or had a peer support component. We examined the extent, nature and distribution of the studies included in this review and determined the following: the majority of studies ( n = 12) used a trial design including randomised controlled trials, pragmatic randomised trials, randomised controlled evaluations, randomised controlled two group design or randomised pilot studies (Charlesworth et al, ; Finkel et al, ; Gaugler et al, , , , ; Gaugler, Reese, Reese, & Mittelman, ; Hayden, Glynn, Hahn, Randall, & Randolph, ; Laakkonen et al, , ; Lai et al, ; Martindale‐Adams, Nichols, Burns, Graney, & Zuber, ; Mittelman et al, ; Núñez‐Naveira et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ; Winter & Gitlin, ), eight studies used a pre/post‐test design (Boots, de Vugt, Withagen, Kempen, & Verhey, ; Chenoweth et al, ; Chu et al, ; Dam, van Boxtel, Rozendaal, Verhey, & de Vugt, ; Gaugler, Hobday, et al, ; Hsu et al, ; Javadpour, Ahmadzadeh, & Bahredar, ; O'Connor, Arizmendi, & Kaszniak, ), four a quasi‐experimental design (Andren & Elmståhl, , ; Easom, Alston, & Coleman, ; Marziali & Garcia, ; Pagán‐Ortiz, Cortés, Rudloff, Weitzman, & Levkoff, ), two a quasi‐experiment with mixed methods design (Baily, Kingsyon, Alford, Taylor, & Tolhurst, ; Küçükgüçlü, Akpınar Söylemez, Yener, & Işık, ) and the final two studies used mixed methods (Hattink, Droes, Sikkes, Oostra, & Lemstra, ; McKechnie, Barker, & Stott, ).…”
Section: Methodsmentioning
confidence: 99%
“…Results demonstrate that it is difficult to deduce if or what components may or may not be effective for dementia carers, with results providing a very mixed landscape in relation to the effectiveness of the differing interventions or corresponding mode of delivery. Overall, of the 36 identified research papers, ten papers reported the assessment of a psychological outcome, however, there is limited evidence on psychological wellbeing impact as significant improvement was reported in only two of these studies (Boots et al, ; Marziali & Garcia, ) both of which were online interventions; 30 research papers reported on feelings of burden/anxiety/depression of these 19 stated a significant improvement (Andren & Elmståhl, ; Chenoweth et al, ; Chu et al, ; Easom et al, ; Finkel et al, ; Gaugler, Reese, et al, ; Gaugler et al, , , ; Hsu et al, ; Javadpour et al, ; Küçükgüçlü et al, ; Marziali & Garcia, ; Núñez‐Naveira et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ; Winter & Gitlin, ); 20 papers provided findings from the assessment of health and well‐being, of these 11 had significant findings (Easom et al, ; Gaugler, Reese, et al, ; Hsu et al, ; Javadpour et al, ; Laakkonen et al, ; Marziali & Garcia, ; Mittelman et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ); six papers reported findings linked to carer satisfaction of which two produced significant findings (Andren & Elmståhl, ; Gaugler, Hobday, et al, ). Finally, 13 papers stated the findings from the assessed level of support, of these five reported significant improvement (Dam et al, ; Gaugler, Reese, et al, ; Marziali & Garcia, ; Wai Tong & Lee, ; Wang et al, ) (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their literature review suggest that diverse forms of support are the most efficient way of achieving social support and welfare goals. According to earlier studies [20,21] informal caregivers found respite in online communities and received emotional support through them. This study's findings on the necessity of peer support reinforce earlier findings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that elderly people also used IC technology in maintaining family relationships and as sources of information on health bulletins as well as various activities [1,16,21].…”
Section: Introduction/backgroundmentioning
confidence: 99%